POLEMIK PUTUSAN MAHKAMAH AGUNG DAN MAHKAMAH KONSTITUSI TERKAIT SYARAT USIA PENCALONAN KEPALA DAERAH - Prakasa Yakub, Sandra Leoni (Bawaslu Provinsi Jawa Barat, 2024)
The main problem in this study is the existence of different interpretations of decisions in judicial institutions testing legislation, between the Supreme Court and the Constitutional Court on the age requirements for nominating regional heads. The approach method used is normative juridical with secondary data collection methods in the form of primary, secondary, and tertiary legal materials. The results showed that when examining the theory and role of the Supreme Court and the Constitutional Court in legislation related to the authority to review laws, it is clear that the decisions of the Constitutional Court are higher. This is because its judgment refers directly to the constitution, thus integrating its decision into the legal framework. The action of the election organizers to uphold the decision of the Constitutional Court is actually a constitutional response, because the Constitutional Court Decision has a higher object and basis of testing in the hierarchy of laws and regulations. In the future, the idea of reforming the instrument or substance of the regulation and the authority of one-stop testing at the Constitutional Court is needed.